Correlation of macronutrient and micronutrient intake with anemia status in pulmonary tuberculosis patients at namorambe community health center - Aritonang Evawany Yunita; Manalu Sarah Patumona; Manalu Samuel MH (BIO Web of Conferences)
Pulmonary TB is an infectious disease that is still a problem, both in diagnosis and treatment, however the success of pulmonary TB treatment is greatly influenced by many factors including the presence of sufferers, comorbidities, smoking habits, food consumption and nutritional status. Namorambe District, Deli Serdang Regency is one of the sub-districts in Deli Serdang which has the highest cases of pulmonary TB, namely 312 cases in 2022. Cure of TB disease is also supported by the health status of TB patients which cannot be separated from nutritional status which is influenced by food consumption, both macro and nutritional nutrients. micronutrients. In theory, there is a relationship between food intake and anemia status and infection, namely that infection will be reduced with good nutritional intake and conversely, infection will be made worse if nutritional intake is not good. This study aims to analyze the relationship between macronutrient and micronutrient consumption and anemia status in pulmonary TB patients. The samples in this study were TB patients in the Deli Serdang Regency health center area who had been confirmed positive for TB and underwent a treatment process for at least one month. The research design used was a survey with a prospective study design. The test for the relationship between the independent variable and the dependent variable was carried out using chi square analysis. The research results showed that 83.35% of people with pulmonary TB were in the very productive age group in terms of income (15-58 years). There were 43.3% of respondents who had abnormal nutritional status. Based on the level of nutritional adequacy, 25 respondents (83.3%) had insufficient energy intake, 18 respondents (60%) had insufficient protein intake, 21 respondents (70%) had insufficient iron intake, and 19 respondents had insufficient zinc intake. less (63.3%). This research shows that the majority of respondents adhere to taking anti-tuberculosis drugs with moderate and high compliance levels of 30% and 63.3% respectively. The results of statistical tests between energy intake and anemia status showed a significance value (P value) of 0.14 (p>0.05). The conclusion in this study is that there is a significant relationship between intake of macronutrients (protein) and micronutrients (zinc and iron) and anemia status in pulmonary tuberculosis sufferers; and there is no significant relationship between energy intake and anemia status in pulmonary tuberculosis patients in the Namorambe Community Health Center Area. Tuberculosis sufferers are at risk of experiencing abnormal body conditions due to a weakened immune system, so it is important for pulmonary tuberculosis sufferers to consume foods that meet their iron needs, such as meat, fish, cultivated vegetables and whole grains.